2021
DOI: 10.1101/2021.12.21.473268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of antiviral drugs against the omicron variant of SARS-CoV-2

Abstract: The Omicron variant of the SARS-CoV-2 virus was first detected in South Africa in November 2021. The analysis of the sequence data in the context of earlier variants suggested that it may show very different characteristics, including immune evasion and increased transmission. These assumptions were partially confirmed, and the reduction in protection in convalescent patients and vaccinated individuals have been confirmed. Here, we have evaluated the efficacy of antivirals against SARS-CoV-2 variants, Omicron,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
(2 reference statements)
2
8
0
Order By: Relevance
“…Therefore, it is not surprising that the observed activity of Nirmatrelvir against these variants was relatively similar. In agreement with our report, two independent groups [14,17] reported that Nirmatrelvir is active against SARS-CoV-2 VOC, further supporting the efficacy of the drug against the circulating SARS-CoV-2 variants, including Omicron. N=number; *=mathematical average (N=2) a. EC50 values for Nirmatrelvir against variants were evaluated using a one-way ANOVA (with USA-WA1 as the fixed effect) and Dunnett test, the p values for the alpha, beta, gamma, lambda and delta variants were 0.9838, 0.0479, 0.9794, 0.8433 and 0.5213, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, it is not surprising that the observed activity of Nirmatrelvir against these variants was relatively similar. In agreement with our report, two independent groups [14,17] reported that Nirmatrelvir is active against SARS-CoV-2 VOC, further supporting the efficacy of the drug against the circulating SARS-CoV-2 variants, including Omicron. N=number; *=mathematical average (N=2) a. EC50 values for Nirmatrelvir against variants were evaluated using a one-way ANOVA (with USA-WA1 as the fixed effect) and Dunnett test, the p values for the alpha, beta, gamma, lambda and delta variants were 0.9838, 0.0479, 0.9794, 0.8433 and 0.5213, respectively.…”
Section: Resultssupporting
confidence: 92%
“…These described biochemical/biophysical results are in line with the equivalent antiviral potency of these molecules against WT and Omicron and the lack of observable differences in the active site. 5 8
Fig. 1 Biochemical and structural comparison of WT and Omicron M pro P132H.
…”
mentioning
confidence: 99%
“…These described biochemical/biophysical results are in line with the equivalent antiviral potency of these molecules against WT and Omicron and the lack of observable differences in the active site. 4-7…”
Section: Resultsmentioning
confidence: 99%